Gram-scale production of graphene based on solvothermal synthesis and sonication - Choucair, Mohammad; Thordarson, Pall; Stride, John A. (Nature nanotechnology, 2009)
Carbon nanostructures have emerged as likely candidates for a wide range of applications, driving research into novel synthetic techniques to produce nanotubes, graphene and other carbon-based materials. Single sheets of pristine graphene have been isolated from bulk graphite in small amounts by micromechanical cleavage 1 , and larger amounts of chemically modified graphene sheets have been produced by a number of approaches 2 , 3 , 4 , 5 , 6 , 7 . Both of these techniques make use of highly oriented pyrolitic graphite as a starting material and involve labour-intensive preparations. Here, we report the direct chemical synthesis of carbon nanosheets in gram-scale quantities in a bottom-up approach based on the common laboratory reagents ethanol and sodium, which are reacted to give an intermediate solid that is then pyrolized, yielding a fused array of graphene sheets that are dispersed by mild sonication. The ability to produce bulk graphene samples from non-graphitic precursors with a scalable, low-cost approach should take us a step closer to real-world applications of graphene. Most techniques for producing graphene use graphite as a starting material and are labour-intensive. The direct chemical synthesis of carbon nanosheets in gram-scale quantities from the common laboratory reagents ethanol and sodium has now been demonstrated. The ability to produce bulk graphene samples from non-graphitic precursors with a scalable, low-cost approach should take us a step closer to real-world applications of graphene.